Flow of Oil and Water through the Nozzle and Cavitation - Jana Jablonská (MDPI AG, 2021)
Today, the correct understanding of the issue of oil and water cavitation is important due to the growing demands on working conditions in hydraulic systems (pressure and flow rate). This article deals with the measurement and subsequent mathematical modeling of cavitation in a convergent-divergent nozzle of circular cross-section. Cavitation depends on the physical properties of the flowing medium as a function of temperature. Usually, cavitation in water is defined by a two-phase flow of water and vapor, but the air contained in the water significantly affects cavitation. There is usually no vapor cavitation in the oil. Far more often, cavitation in oil is caused by the air it contains. For comparison, cavitation in water and oil was generated in experiments with an identical nozzle. The measurement was used to define boundary conditions in mathematical models and to verify simulations. The problem of cavitation was solved by three variants of multiphase flow, single-phase flow (water, oil), two-phase flow (water–vapor, oil–air) and three-phase flow (water–vapor–air, oil–vapor–air). A turbulent model with cavitation was used for all variants. The verification of simulations shows that for water cavitation it is necessary to use a three-phase model (water, vapor, air) and for oil cavitation a two-phase model (oil, air) is sufficient. The measurement results confirm the importance of the air phase in modeling cavitation in both water and oil.